1990
DOI: 10.1080/00365519009085803
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous interference in imunoassays in clinical chemistry. A rewiev

Abstract: Weber TH, Kapyaho KI & Tanner P Endogeneous interference in immunoassays in clinical chemistry. A review. Scand . I Clin Lab Invest 1990; 50, Suppl201: 77-82.The increasing availability and use of immunoassays in clinical chemistry have revealed a number of endogeneous interferences. Solid-phase sandwich immunoassays based on monoclonal antibodies are particularly sensitive to any factor able to bridge immunoglobulins together. Heterophilic immunoglobulin antibodies have been demonstrated in up to 40 % of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 35 publications
0
26
0
1
Order By: Relevance
“…Therefore, it is routine practice for assay manufacturers to incorporate the serum of nonimmune animal species in the reagents of most methods. Bovine serum has been shown to be more efficient than murine serum (29). It has been suggested that heterophilic antibodies in most patients are bovine IgGs arising from the ingestion of meat and milk (13).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is routine practice for assay manufacturers to incorporate the serum of nonimmune animal species in the reagents of most methods. Bovine serum has been shown to be more efficient than murine serum (29). It has been suggested that heterophilic antibodies in most patients are bovine IgGs arising from the ingestion of meat and milk (13).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of heterophilic antibodies in samples of human serum or plasma in the population was estimated at 30%-40% (29,30). Their concentration in the blood and detectability by using different methods depend on the type of antibody.…”
Section: Interference From Heterophilic Antibodies 761 Nomenclaturementioning
confidence: 99%
“…Various immunoassay buffer additives may reduce interference from heterophilic antibodies. Although mouse IgG is most frequently used in the currently accessible noncompetitive immunoassays, bovine serum has been shown to be more efficient than murine serum in blocking heterophilic antibodies (72). Practically no information on this matter can be found in the literature.…”
Section: Use Of Buffer Additivesmentioning
confidence: 99%
“…Fragments, rather than the intact antibody, have been used in an attempt to reduce interference from antibodies against the Fc region, which are produced in some conditions such as autoimmune disease. 8,11,42 However, because interfering antibodies mainly interact with binding sites on the Fab region, the use of a fragment rather than the entire antibody as a reagent may reduce, but not eliminate, insidious interference.…”
Section: Antibodies As Reagentsmentioning
confidence: 99%